USE AND ANALYSIS OF 3D BIOPRINTER IN EXAMINATION OF HUMAN INTERNAL ORGANS AND CREATION OF THEIR MODELS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The use of 3D bioprinting technology has revolutionized the way we examine human internal organs and create models for research and medical purposes. This paper presents a comprehensive analysis of the use of 3D bioprinter in examination of human internal organs and creation of their models. The study focuses on the different techniques used in 3D bioprinting technology, and the challenges associated with its use. The paper also highlights the advantages and limitations of 3D bioprinting technology in creating models of human internal organs.